Inhibitory effects of Lactobacillus casei Shirota against both Candida auris and Candida spp. isolates that cause vulvovaginal candidiasis and are resistant to antifungals - Aline Lorenzoni Paniágua; Amabel Fernandes Correia; Lívia Custódio Pereira; Bruna Maciel de Alencar; Fabiana Brandão Alves Silva; Rosane Mansan Almeida; Yanna Karla de Medeiros Nóbrega (BMC, 2021)
Abstract Background Vulvovaginal candidiasis (VVC), the second leading cause of genital infection in women of reproductive age, is caused by yeasts of the genus Candida. Treatment is usually empirical and performed with azoles, which have shown increasing ineffectiveness due to resistance from these species. This therapeutic challenge has led to the search for new treatment strategies. Lactobacillus spp. produce several components with microbicidal effects, such as lactic acid. These species are the main components of a healthy vaginal microbiota and have been used as probiotics. The aim of this work was to investigate the in vitro inhibitory effects of Lactobacillus casei Shirota on both the Candida spp. that cause VVC and on C. auris. Methods The microbicidal effects of L. casei Shirota on the main VVC-causing species, C. albicans, C. tropicalis, C. norvegensis and C. parapsilosis, in addition to C. auris were investigated by counting the Colony-forming Units (CFUs) after cocultivation. The antifungal activity of lactic acid against these Candida strains was assessed using the microtiter broth dilution method to determine the minimum inhibitory concentrations (MICs). The effects of L. casei Shirota on hyphal and early biofilm formation was measured by optical microscopy. Results L. casei Shirota showed inhibitory action against all tested Candida spp., ranging from 66.9 to 95.6% inhibition depending on the species. This inhibition is possibly related to the production of lactic acid, since lactic acid has shown microbicidal action against these same Candida spp. at a concentration of 5 mg/mL, which corresponds to half of the normal physiological concentration. In addition, L. casei Shirota was able to reduce the formation of C. albicans hyphae and early biofilms, showing strong anti-Candida effects. Conclusions These results suggest that L. casei Shirota has antifungal activity against the Candida species that cause VVC. L. casei also has microbicidal action against C. auris.